Who are the Breast Cancer survivors in Malaysia? - Ibrahim, N.I.; Dahlui, M.; Aina, E.N.; Al-Sadat, N. (2012)
Introduction: Worldwide, breast cancer is the commonest cause of cancer death in women. However, the survival rate varies across regions at averages of 73 and 57 in the developed and developing countries, respectively. Objective: This study aimed to determine the survival rate of breast cancer among the women of Malaysia and characteristics of the survivors. Method: A retrospective cohort study was conducted on secondary data obtained from the Breast Cancer Registry and medical records of breast cancer patients admitted to Hospital Kuala Lumpur from 2005 to 2009. Survival data were validated with National Birth and Death Registry. Statistical analysis applied logistic regression, the Cox proportional hazard model, the Kaplan-Meier method and log rank test. Results: A total of 868 women were diagnosed with breast cancer between January 2005 and December 2009, comprising 58, 25 and 17 Malays, Chinese and Indians, respectively. The overall survival rate was 43.5 (CI 0.573-0.597), with Chinese, Indians and Malays having 5 year survival rates of 48.2 (CI 0.444-0.520), 47.2 (CI 0.432-0.512) and 39.7 (CI 0.373-0.421), respectively (p<0.05). The survival rate was lower as the stages increased, with the late stages were mostly seen among the Malays (46), followed by Chinese (36) and Indians (34). Size of tumor>3.0cm; lymph node involvement, ERPR, and HER 2 status, delayed presentation and involvement of both breasts were among other factors that were associated with poor survival. Conclusions: The overall survival rate of Malaysian women with breast cancer was lower than the western figures with Malays having the lowest because they presented at late stage, after a long duration of symptoms, had larger tumor size, and had more lymph nodes affected. There is an urgent need to conduct studies on why there is delay in diagnosis and treatment of breast cancer women in Malaysia.